Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

If we define the 2-form $\omega=\frac{1}{r^3}(x_1dx_2\wedge dx_3+x_2dx_3\wedge dx_1+x_3dx_1\wedge dx_2)$ with $r=\sqrt{x_1^2+x_2^2+x_3^2}$

If we now define $x(\theta,\phi)=(\sin\theta\cos\phi,\sin\theta\sin\phi,\cos\theta)$ for $\theta\in(0,\pi)$ and $\phi\in (0,2\pi)$

I now want to show that the pullback of this map is:

$x^*\omega=\sin\theta d\theta\wedge d\phi$

Now my definition of the pullback of a map $c:[a,b]\rightarrow D$ is $\alpha(c'(t))dt$ but am unsure as to how to proceed? I can see that this curve $x$ is a parametrization of the sphere in $\mathbb{R}^3$ but after that I am a bit lost?

Thanks for any help

share|improve this question
2  
simply plug the expressions for $x_{1,2,3}$ in terms of $\theta,\phi$ into $\omega$ and calculate the resulting form. –  O.L. May 22 '13 at 9:36
    
@O.L. sorry I am confused as to how I evalute $x'(t)$ what it is in terms of $\theta$ and $\phi$? –  hmmmm May 22 '13 at 9:54
2  
@hmmmm: What O.L. means is this: You should plug in $x_1 = \sin \theta \cos \phi$ and $x_2 = \sin\theta \sin \phi$, and so on. Then, for example, $$dx_1 = d(\sin\theta \cos\phi) = d(\sin\theta)\cos\phi + \sin\theta \,d(\cos\phi) = \cos\theta \cos \phi\, d\theta - \sin\theta\sin\phi \,d\phi.$$ Similarly for the others. –  Jesse Madnick May 22 '13 at 10:07
    
I guess $c(t)$ appeared in a one-dimensional example which is not very much related to your question. Here, instead of a curve mapped to some space, you have a surface (2D sphere). In a sense, the analog of $t$ here is the pair $(\theta,\phi)$, and the analog of $c$ is given by the triple of functions $x_{1,2,3}(\theta,\phi)$. –  O.L. May 22 '13 at 10:10

1 Answer 1

up vote 2 down vote accepted

A more general equation for how to compute pullbacks is as follows: If $f: M \to N$ is a smooth map of smooth manifolds and $\omega$ is an $n$-form on $N$, written in local coordinates as $$ \omega = \sum_I \omega_I dy^{i_1} \wedge \cdots \wedge dy^{i_n}$$ then $f^*\omega$ can be written in induced coordinates as $$ f^*\omega = \sum_I (\omega_I \circ f) d(y^{i_1} \circ f) \wedge \cdots \wedge d(y^{i_n} \circ f)$$ where you think of $y^i$ as the function which picks out the $i^{th}$ coordinate of $f$.

Your $\omega$ is given by $$ \omega = \omega_{23} dx_2 \wedge dx_3 + \omega_{31} dx_3 \wedge dx_1 + \omega_{12} dx_1 \wedge dx_2$$ where $\omega_{23} = \frac{x_1}{r^3}, \omega_{31} = \frac{x_2}{r^3}$ andd $\omega_{12} = \frac{x_3}{r^3}$. So now you just use the formula: I will do the $\omega_{23} dx_2 \wedge dx_3$ term as an example:

$$ f^*(\omega_{23} dx_2 \wedge dx_3) = (\omega_{23} \circ f) d(x_2 \circ f) \wedge d(x_3 \circ f) $$

Now \begin{align*} \omega_{23} \circ f &= \frac{\sin\theta \cos\phi}{\sqrt{\sin^2\theta\cos^2\phi + \sin^2\theta \sin^2\phi + \cos^2\phi}^3} = \sin\theta\cos\phi \\ d(x_2\circ f) &= d(\sin\theta\sin\phi) = \cos\theta \sin\phi d\theta + \sin\theta \cos\phi d\phi \\ d(x_3\circ f) &= d(\cos\theta) = -\sin\theta d\theta. \end{align*} Putting it all together, we get \begin{align*} (\omega_{23} \circ f) d(x_2 \circ f) \wedge d(x_3 \circ f) &= (\sin\theta\cos\phi)(\cos\theta\sin\phi d\theta + \sin\theta\cos\phi d\phi) \wedge (-\sin\theta d\theta ) \\ &= \sin^3\theta\cos^2\phi d\theta \wedge d\phi \end{align*}

(Of course, modulo mistakes in my computations!)

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.